A comparative analysis of oral and maxillofacial pathology over a 16‐year period, in the north of Portugal. (29th September 2016) - Monteiro, Luís S.; Albuquerque, Rui; Paiva, António; de la Peña‐Moral, Jesús; Amaral, José B.; Lopes, Carlos A.
Abstract : Objectives: To determine the frequency and spectrum of oral and maxillofacial lesions biopsied in a hospital population in the northern region of Portugal. Methods: We conducted descriptive analyses of pathology reports from biopsies of oral and maxillofacial lesions performed between 1990 and 2006, in Oporto Hospital Center. Information on gender and age of patient, location of the lesions and the histopathological diagnosis were analysed. Results: The analyses revealed that 1, 520 (47.7%) patients were male and 1, 666 (52.3%) were female. They had a mean age ± standard deviation of 47.8 ± 18.6 years. The site most frequently biopsied was the labial mucosa (17.5%). A non‐neoplastic diagnosis was established in 2, 162 (63.3%) cases, potentially malignant disorders in 163 (5.1%) and neoplasms in 886 (27.6%) (403 benign and 483 malignant). The most commonly reported diagnosis was fibroepithelial polyp ( n = 186; 15.9%), followed by squamous cell carcinoma (SCC) ( n = 158; 13.6%). SCC was the lesion most commonly found in male patients ( n = 279; 18.4%) whilst fibroepithelial polyp was the lesion most commonly found in female patients ( n = 268; 16.1%). The most common lesion in patients 0–17 years of age was a follicular cyst ( n = 25; 12.8%), whereas in patients 18–64 years of age it was a fibroepithelial polyp ( n = 299; 13%). SCC was the most common type of lesion found in patients ≥ 65 years of age ( n = 160; 24.6%). Conclusion: This large sample provides useful information about the incidence and distribution of oral biopsies over a period of 16 years, allowing valuable comparison with other countries. Non‐neoplastic lesions were the types of lesion most commonly reported, with fibroepithelial polyp being most frequent. SCC was the second most common diagnosis.